Mutu Teripang Selama Penyimpanan Pada Suhu Es - Siti Rahayu; Mei Dwi Erlina; Murniyati Murniyati (agriTECH, 1993)
Study on the quality deterioration of sea cucumber in ice temperature was carried out. Two kinds of sea cucumber i.e. sand sea cucumber (Holothuria scraba) and rock sea cucumber (Microthele oxiloga HI, Clark) boiled and the raw were stored in crushed ice using insulated box. During storage, assessment of organoleplic properties (appearance, color, odor and texture), chemical analysis (moisture, ash, protein, fat, pH, TVB) and microbiology analysis (total bacteria and total enterobacteriacea) were conducted every three days. The results indicated that the organoleptic scores (appearance, color, odor and texture) decreased, while pH, TVB, total bacteria and enterobacteriaceae increased during storage. This study has shown that the quality boiled sea cucumber was better than raw sea cucumber, where the First was still accepted by the panelist 15 days, storage while the later was rejected after 12 days storage.